2010
DOI: 10.1016/j.rmed.2010.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution and children's respiratory symptoms in six cities of Northern China

Abstract: The high levels of outdoor air pollution in north China are positively associated with children's respiratory symptoms, the associations with TSP appear to be stronger than SO(2) and NO(2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 28 publications
2
49
0
2
Order By: Relevance
“…Environmental factors, such as air pollution, may be responsible. High levels of outdoor air pollution are positively associated with persistent cough in China [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Environmental factors, such as air pollution, may be responsible. High levels of outdoor air pollution are positively associated with persistent cough in China [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Dong et al (2011), the associations were reduced from an OR of 1.19 (95% CI: 1.06-1.34) per 10 μg/m 3 in males and an OR of 1.14 (95% CI: 0.99-1.30) in females to an OR of 0.97 for both sexes in a five-pollutant model. In Pan et al (2010), the effect estimates for current asthma associated with NO 2 were strongly reduced and lost statistical significance in a three-pollutant model with total suspended particulates and SO 2 (total suspended particulates and NO 2 were correlated with r = 0.6). Sahsuvaroglu et al (2009) investigated asthma prevalence in schoolchildren in Hamilton, Canada.…”
Section: Long Term Effects On Asthmamentioning
confidence: 92%
“…There are also a range of cross-sectional studies that investigated within-community exposure contrasts, more representative of traffic pollution, which have not been reviewed here, but include many positive associations with NO 2 , some of which are statistically significant. Three of the recent area studies on asthma prevalence included multipollutant models (Dong et al, 2011;Pan et al, 2010;Sahsuvaroglu et al, 2009). In the study by Dong et al (2011), the associations were reduced from an OR of 1.19 (95% CI: 1.06-1.34) per 10 μg/m 3 in males and an OR of 1.14 (95% CI: 0.99-1.30) in females to an OR of 0.97 for both sexes in a five-pollutant model.…”
Section: Long Term Effects On Asthmamentioning
confidence: 99%
“…Surrounded by mountains, the climate of LanzhouXigu is characterized by very stable atmospheric stratification with strong atmospheric inversion extending to the afternoon which hinders the diffuse out of air pollutants. Heavy PAHs emissions have been occurring in Xigu (Zhang et al 2000;Pan et al 2010;Gao et al 2007;Tao et al 2012). It has been reported that cancer-standardized rate of local population in Xigu was the highest (192.84/10) in Lanzhou (Zhang et al 2011).…”
Section: Targeted Populationmentioning
confidence: 99%